The meaning of everything the story of the Oxford English Dictionary - Winchester, Simon 1944- (Oxford Univ. Press, 2003)
Traces the history of the Oxford English Dictionary from its earliest inception through its long path to completion, describes the process of creating a dictionary, and includes anecdotes about its creators and their work.
Keywords: Murray, James Augustus Henry -- Sir -- 1837-1915; Furnivall, Frederick James -- 1825-1910; Coleridge, Herbert -- 1830-1861; Oxford English dictionary; The Oxford English dictionary; Geschichte 1800-1900; Geschichte; Anglais (Langue) - Lexicographie - Histoire; Engels; Oxford English dictionary (anoniem); Woordenboeken; Englisch; English language -- Lexicography -- History -- 19th century; Lexicographers -- Great Britain -- Biography; Lexikografie; Großbritannien; Biografie